DAMPAK PANDEMI COVID-19 TERHADAP KEUNTUGAN USAHA NASI KUNING KIOS YU CHIA DI KELURAHAN BANJER KECAMATAN TIKALA KOTA MANADO - Lumintang, Friski Kiki; Loho, Agnes Estephina; Waney, Nordy Fritsgerald Lucky (Sam Ratulangi University, 2022)
This study aims to determine the impact of the Covid-19 pandemic on the Yu Chia yellow rice stall Business Profits in Banjer Village, Tikala District, Manado City. This research was carried out from July to September 2021. The data used were primary data and secondary data. Primary data were collected through interviews, giving questionnaires, and direct observation to the owner of the Yu Chia Kiosk business. While secondary data was taken from previous research that took data before the pandemic. The results showed that the impact of the Covid-19 pandemic had slightly changed the recipe used, the decrease in profit per unit decreased by 73.29% compared to before the covid-19 pandemic. The Covid-19 pandemic had no effect on the recipe used in making yellow rice because Yu Chia yellow rice stall wanted to maintain quality and characteristics of yellow rice.